Adaptive cross-country optimization strategies in thermal soaring birds - Göksel Keskin; Olivier Duriez; Pedro Lacerda; Andrea Flack; Máté Nagy (iScience)
Summary: Thermal soaring enables birds to perform cost-efficient flights. Although aerodynamic rules dictate the costs of flight, soaring species vary strongly in their morphologies and behavioral strategies. To quantify morphology-related differences in behavioral cross-country strategies, we analyzed a large dataset consisting of over a hundred individuals from 12 soaring species recorded with high-frequency tracking devices. We quantified their performance during thermalling and gliding flights and their overall cross-country behavior. Our results confirmed aerodynamic theory across the species; species with higher wing loading typically flew faster and consequently turned on a larger radius than lighter ones. Furthermore, the combination of circling radius and minimum sink speed determines the maximum benefits soaring birds obtain from thermals. Notably, we observed a spectrum of strategies regarding the adaptivity to thermal strength and uncovered a universal rule for cross-country strategies for all analyzed species which can provide inspiration for technical applications, like autopilot for robotic gliders.